Comparative phytochemicals screening and estimation of constituents present in the leaves of Decalepis species through HPLC - Kuntal Das; Syed Mohammed Basheeruddin Asdaq; Sravani Singirikonda; M. Saifulla Khan; Abdulhakeem S. Alamri; Walaa F. Alsanie; Majid Alhomrani; Farhana Yasmin (Journal of King Saud University: Science, 2022)
Background and objectives: The variation in the active phytoconstituents in different plants causes changes in their biological properties. The present study was aimed with the comparative phytochemicals and estimation of the constituent present in the leaves of Decalepis species using high performance liquid chromatography (HPLC). Materials and Methods: The leaves of Decalepis hemiltonii Wight & Arn. Decalepis arayalpathra(J. Joseph and V. Chandras.) Venter. and Decalepis nervosa(Wight &Arn.) Venter.were selected and methanol solvent was used for the preparation of the extracts. Various proximate analysis viz. moisture content, ash values, crude fibers, extractive values were estimated. Thereafter, series of basic chemical tests for the methanol leaves extracts followed by total phenolics, and total flavonoids content were also carried out. Furthermore, TLC chromatogram and RP-HPLC study was carried out for all the plant extracts to find out the presence of phenolic compounds and compared the estimated amount present in all the leaves extracts. Results: The outcome of the study revealed that all the three species varied with the yield and the phytochemical screening showed varied concentration of alkaloids, glycosides, flavonoids, proteins, steroids, phenols, and tannins. Among the three species Decalepis hemiltonii(DH) showed presence of higher percentage of moisture (8.6%), crude fibers (8.32%) and total ash content (4.95%) than others. Further, presence of high concentration of phytochemicals was showed by Decalepis arayalpathra (DA) and the higher yield in methanol solvent than other two species. The same plant sample showed presence of higher amount of gallic acid (0.86 mg/100 g) than other two species. Total alkaloids, total phenolic and total flavonoids were higher in DA leaves flowed by Decalepis nervosa (DN) and DH leaves samples. Interpretation: Overall the results indicated that DA leaves extracts was better in terms of yield, presence of phytoconstituents, presence of total alkaloids, total flavonoids, and total phenolics and presence of gallic acid followed by DN and DH leaves.